2001
DOI: 10.1007/s12043-001-0140-7
|View full text |Cite
|
Sign up to set email alerts
|

A plethora of strange nonchaotic attractors

Abstract: We show that it is possible to devise a large class of skew-product dynamical systems which have strange nonchaotic attractors (SNAs): the dynamics is asymptotically on fractal attractors and the largest Lyapunov exponent is nonpositive. Furthermore, we show that quasiperiodic forcing, which has been a hallmark of essentially all hitherto known examples of such dynamics is not necessary for the creation of SNAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Furthermore, explicit quasiperiodic driving is also a feature of hitherto studied systems. However, both these features are probably not necessary in order that SNAs be formed [Negi and Ramaswamy, 2000a]. In particular, driving a system with signals based on fractal sequences also appears to yield SNAs [Kuptsov, 1998].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, explicit quasiperiodic driving is also a feature of hitherto studied systems. However, both these features are probably not necessary in order that SNAs be formed [Negi and Ramaswamy, 2000a]. In particular, driving a system with signals based on fractal sequences also appears to yield SNAs [Kuptsov, 1998].…”
Section: Discussionmentioning
confidence: 99%
“…Mathematically rigorous results are more difficult in this case, but there is some indication that it will be possible to have fractal nonchaotic attractors in a large class of systems, even in the absence of explicit quasiperiodic driving [Negi and Ramaswamy, 2000a].…”
Section: Strange Nonchaotic Dynamics: Occurrence and Characterizamentioning
confidence: 99%
“…In subsequent years, there have been several experimental observations of SNAs in practical systems [11][12][13][14][15]; however, all these studies presented the necessity of having quasiperiodic forcing to generate SNAs. While these previous investigations on SNA involved external quasiperiodic forcing, Negi et al [16] theoretically showed that quasiperiodic forcing is not essential for the existence of SNA, and it could happen in naturally driven systems as well without the need of external forcing. Recently, Lindner et al [17] showed the observation of SNAs in the natural system of a pulsating star KIC 5520878 network.…”
mentioning
confidence: 99%
“…We can however do even better than this by ensuring that all components of the system are piecewise linear. In [18] a similar piecewise linear system was studied of the form…”
Section: Making the Argument Exact: Piecewise Linear Snasmentioning
confidence: 99%